Selected abstracts from the Breastfeeding and Feminism International Conference 2016 - Lisa H. Amir; Alessandra Bazzano; Shelley Thibeau; Katherine P. Theall; Anna Blair; Karin Cadwell; Emily A. Bronson; Elizabeth C. Brooks; Jodine Chase; Ellen Chetwynd; Rebecca Costello; Kathryn Wouk; et al. (BMC, 2016)
Table of contents A1. Infant feeding and poverty: a public health perspective in a global context Lisa H. Amir A2. Mothers' experiences with galactagogues for lactation: an exploratory cross sectional study Alessandra Bazzano, Shelley Thibeau, Katherine P. Theall A3. The motherhood journey and breastfeeding: from self-efficacy to resilience and social stigma Anna Blair, Karin Cadwell A4. Breastfeeding as an evolutionary adaptive behavior Emily A. Bronson A5. Conflict-of-interest in public health policy: as real as that logo on your website Elizabeth C. Brooks A6. Co-opting sisterhood and motherhood: behind the scenes of Similac's aggressive social media campaigns Jodine Chase A7. The exclusion of women from the definition of exclusive breastfeeding Ellen Chetwynd, Rebecca Costello, Kathryn Wouk A8. Healthy maternity policies in the workplace: a state health department's experience with the "Bring Your Infant to Work" program Lindsey Dermid-Gray A9. Implications for a paradigm shift: factors related to breastfeeding among African American women Stephanie Devane-Johnson, Cheryl Woods Giscombe, Miriam Labbok A10. Social experiences of breastfeeding: building bridges between research and policy: an ESRC-funded seminar series in the UK Sally Dowling A11. Manager's perspectives of lactation breaks Melanie Fraser A12. The challenging second night: a dialogue from two perspectives Jane Grassley, Deborah McCarter-Spaulding, Becky Spencer A13. The role of lactation consultants in two council breastfeeding services in Melbourne, Australia - some preliminary impressions Jennifer Hocking, Pranee Liamputtong A14. Integrating social marketing and community engagement concepts in community breastfeeding programs Sheree H. Keitt, Harumi Reis-Reilly A15. What happens before and after the maternity stay? Creating a community-wide Ten Steps approach Miriam Labbok A16. #RVABREASTFEEDS: cultivating a breastfeeding-friendly community Leslie Lytle A17. Public health vs. free trade: a longitudinal analysis of a global policy to protect breastfeeding Mary Ann Merz A18. Legislative advocacy and grassroots organizing for improved breastfeeding laws in Virginia Kate Noon A19. Breastfeeding and the rights of incarcerated women Krista M Olson A20. Barriers and support for Puerto Rican breastfeeding working mothers Ana M. Parrilla-Rodríguez, José J. Gorrín-Peralta Melissa Pellicier, Zeleida M. Vázquez-Rivera A21. Pumping at work: a daily struggle for Puerto Rican breastfeeding mothers in spite of the law Melissa Pellicier A22. "I saw a wrong and I wanted to stand up for what I thought was right:" a narrative study on becoming a breastfeeding activist Jennifer L. Pemberton A23. Peer breastfeeding support: advocacy and action Catherine McEvilly Pestl A24. Good intentions: a study of breastfeeding intention and postpartum realities among first-time Central Brooklyn mothers Jennifer Pierre, Philip Noyes, Khushbu Srivastava, Sharon Marshall-Taylor A25. Women describing the infant feeding choice: the impact of the WIC breastfeeding classes on infant feeding practices in Ionia, Michigan Jennifer Proto, Sarah Hyland Laurie Brinks A26. Local and state programs and national partnership to reduce disparities through community breastfeeding support Harumi Reis-Reilly, Martelle Esposito, Megan Phillippi A27. Beyond black breastfeeding week: instagram image content analysis for #blackwomendobreastfeed/#bwdbf Cynthia L. Sears, Delores James, Cedric Harville, Kristina Carswell A28. Stakeholder views of breastfeeding education in the K-12 environment: a review of the literature Nicola Singletary, L. Suzanne Goodell, April Fogleman A29. "The Breastfeeding Transition": a framework for explaining changes in global breastfeeding rates as related to large-scale forces shaping the status of women Paige Hall Smith A30. Breastfeeding, contraception, and ethics, oh my! Advocacy and informed decision-making in the post-partum period Alison M. Stuebe, Amy G. Bryant, Anne Drapkin Lyerly A31. A hard day's night: juggling nighttime breastfeeding, sleep, and work Cecilia Tomori A32. Empowering change in Indian country through breastfeeding education Amanda L. Watkins, Joan E. Dodgson A33. Servants and "Little Mothers" take charge: work, class, and breastfeeding rates in the early 20th-century U.S. Jacqueline H. Wolf